Effectiveness of influenza vaccine in children in preventing influenza associated hospitalisation, 2018/19, England. Issue 2 (10th January 2020) - Pebody, R.G.; Zhao, H.; Whitaker, H.J.; Ellis, J.; Donati, M.; Zambon, M.; Andrews, N.
Abstract: 2013/14 saw the start of the introduction of a new live attenuated influenza vaccine (LAIV) programme for children in England. 2018/19 saw co-circulation of both A(H1N1)pdm09 and A(H3N2), when LAIV was offered to all healthy children 2–9 years of age. LAIV effectiveness against influenza hospitalisation is not well described. This paper presents the 2018/19 end-of-season adjusted vaccine effectiveness (aVE) against laboratory confirmed influenza related hospitalisation in children aged 2–17. The test negative case control approach was used to estimate aVE by influenza A subtype and vaccine type. Cases and controls were selected from a sentinel laboratory surveillance system which collates details of individuals tested for influenza with reverse-transcription polymerase chain reaction (RT-PCR) on respiratory samples. Vaccine and clinical history was obtained from general practitioners of study participants. There were 307 hospitalised cases and 679 hospitalised controls. End-of-season influenza aVE was 53.0% (95% CI: 33.3, 66.8) against influenza confirmed hospitalisation; 63.5% (95% CI: 34.4, 79.7) against influenza A(H1N1)pdm09 hospitalisation and 31.1% (95% CI: −53.9, 69.2) against influenza A(H3N2). LAIV aVE was 49.1% (95% CI: 25.9, 65.0) for any influenza and 70.7% (95% CI: 41.8, 85.3) for A(H1N1)pdm09, whereas for those receiving quadrivalent inactivated influenza vaccine (QIV), aVE was 64.4% (95% CI: 29.4, 82.0) and 44.4% (95% CI: −51.9, 79.6) respectively. We provide evidence of overall significant VE for both LAIV and QIV against influenza associated hospitalisation in children 2–17 years of age, most notably against influenza A(H1N1)pdm09, with non-significant protection against A(H3N2).